RELEVANCE OF VO2max CONSUMPTION IN ELITE BULGARIAN TAEKWONDO COMPETITORS - Dimitar Avramov (Scientific Publishing House. NSA Press, 2021)
The aim of this study was to determine aerobic fitness through the VO2 max treadmill test of elite Bulgarian taekwondo players with international results, and to determine whether the aerobic system had an effect upon the sports result in taekwondo. Fourteen elite taekwondo athletes, members of the Bulgarian national team (8 male and 6 female) were tested using a continuous progressive treadmill test. Physiological characteristics such as maximal oxygen uptake (VO2 max), blood lactate and heart rate were measured. The male athletes recorded 58.2±3.4 ml kg-1 min-1 and the female 46.0±2.8 ml kg-1 min-1. The lactate level reached its highest at the 6' after the VO2 maxwith results for the males of 11.5±3.7 (mmol l-1) and 9.9±4.1 (mmol l-1) for the females respectively. A comparison between our results, regarding VO2 max and previously reported was made using the One-way Anova for independent samples. It showed no significant difference between the male subjects (58.2±3.4 versus 60.7±3.3 ml kg(-1) min(-1), p>.05) and significant difference between the female ones (46.0±2.8 versus 49.8±2.8 ml kg(-1) min(-1), p<.05). Investigated also was the number of kicks executed by the winner of -49 kg weight category and her direct opponents during the 2019 Grand Prix Sofia. It was discovered that the winner kicked an average of 86.25 times per match and her kicks during the Grand Prix Sofia accumulated to 390 in total. It is our conclusion that the aerobic fitness does not play a significant role in taekwondo.